(untitled) (Fiep Bulletin - online, 2015)
Obesity is one of the most serious public health problems in the world, growing progressively and quickly is a non-communicable disease. It is observed that the level / duration of physical activity practiced is decreasing, increasing the number of sedentary individuals and contributing to the rise in obesity. The aim was to analyze the values ??of waist circumference, body mass index, physical inactivity, related to age and sex. The study was conducted with officials from the Federal University of Minas Gerais, during the blitz of health in a sample of 196 participants - 132 men and 64 women 16-83 years of sectional study in which we applied the questionnaire thresholds risk factors for atherosclerotic disease were measured and the body mass index (IMB), abdominal circumference (AC) and a sedentary lifestyle of each participant. To examine associations between obesity and physical inactivity x2 test was used. 50.75% of women are sedentary and men represent 40.62%. 23.48% women and 29.68% of men are overweight or obese. 40.90% women and 21.87% of men had increased / greatly increased cardiovascular risk. Regarding age groups, showed higher CA and overweight / obese group 55 years and above for women and men for the same age group had the highest percentage inactivity. In females fall in the values ??of physical inactivity were related to declines in value of CA. With increasing age in the percentage of sedentary people has also increased in both sexes. The increasing trend of overweight and obesity in our population and the strong association with these cardiovascular risk factors are important interventions to reduce body weight, particularly abdominal fat so there is the prevention and control of cardiovascular diseases in the population.